?SYNTHESIS OF NEW CYCLIC PYRAZOLONESULFONYL THIOANALOGES OF POSSIBLE PHARMACOLOGICAL ACTIVITY - MAKKI, MOHAMMAD S.I.; FAIDALLAH, HASSAN M. (Biological Sciences - PJSIR, 1995)
Condensation ofbenzenesulphonylthiourea derivatives 1with halogeno esters in absolute ethanol afforded the corresponding iminoesters 2-4, while in glacialacetic acid they yielded the thiazolidinone and the thiazinone deriva- tives6 and7. Reactionof4 witharylhydrazinesaffordedthethiadiazines5. Cyc1izationof 1 witho-brornoacetophenones yielded the thiazolines 8.